2020
DOI: 10.1038/s41366-020-00694-1
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes is associated with impaired jejunal enteroendocrine GLP-1 cell lineage in human obesity

Abstract: Objectives Altered enteroendocrine cell (EEC) function in obesity and type 2 diabetes is not fully understood. Understanding the transcriptional program that controls EEC differentiation is important because some EEC types harbor significant therapeutic potential for type 2 diabetes. Methods EEC isolation from jejunum of obese individuals with (ObD) or without (Ob) type 2 diabetes was obtained with a new method of cell sorting. EEC transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 61 publications
0
35
1
Order By: Relevance
“…Furthermore, the increase in jejunal GLP-1 + cell number after VSG might have clinical implications. A recent study revealed that jejunal GLP-1 + cell number is decreased in obese patients (even more so in obese patients with T2DM) compared to non-obese individuals 35 . Jejunal EECs isolated from patients with T2DM also demonstrate downregulation in genes involved in EEC differentiation (including PAX4 and FOXA2 ) and in the GCG gene itself 35 , indicating that jejunal GLP-1 + cell differentiation and number are negatively impacted by both obesity and T2DM.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the increase in jejunal GLP-1 + cell number after VSG might have clinical implications. A recent study revealed that jejunal GLP-1 + cell number is decreased in obese patients (even more so in obese patients with T2DM) compared to non-obese individuals 35 . Jejunal EECs isolated from patients with T2DM also demonstrate downregulation in genes involved in EEC differentiation (including PAX4 and FOXA2 ) and in the GCG gene itself 35 , indicating that jejunal GLP-1 + cell differentiation and number are negatively impacted by both obesity and T2DM.…”
Section: Discussionmentioning
confidence: 98%
“…The expression profiling by high throughput sequencing data GSE132831 was downloaded from the GEO database, which was based on the platform of GPL1857 Illumina NextSeq 500 (Homo sapiens). This dataset, including 104 diabetic obese samples and 120 non diabetic obese samples, was deposited by Osinski et al [12].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in this investigation, we downloaded the expression profiling by high throughput sequencing data GSE132831, provided by Osinski et al [12], from Gene Expression Omnibus (GEO, http://www.ncbi.nlm.nih.gov/geo/) [13] database to identify the differentially expressed genes (DEGs) between diabetic obese samples and non diabetic obese samples. With the identified DEGs, we performed Gene Ontology (GO) and pathway enrichment analyses to investigate the functions and pathways enriched by the DEGs.…”
Section: Introductionmentioning
confidence: 99%
“…31 In humans, postprandial GLP-1 levels are somewhat lowered in obese individuals with or without T2D. 32,33 In addition, the density of GLP-1-positive cells and differentiation of jejunal GLP-1-expressing cells are reduced in obese individuals with T2D, 22 indicating that the function of GLP-1-expressing EECs is affected by diabetic Gut microbiota produces a number of microbial metabolites that interact with intestinal enteroendocrine cells to modulate hormone secretion and expression. Changes in the gut microbiota composition either by consumption of dietary fiber or bariatric surgery procedures (such as Roux-en-Y gastric bypass or vertical sleeve gastrectomy) modulate levels of microbial metabolites, which in turn affect the enteroendocrine cells.…”
Section: Glp-1 and Pyymentioning
confidence: 99%
“…Enteroendocrine cells (EECs) constitute a highly specialized population of chemosensory intestinal cells 21 and provide a unique platform to study cellular interaction with the gut microbiota. Dysregulation of EECs is evident in metabolic diseases 22 that make them important drug targets. Currently, the gut hormone glucagon-like peptide-1 (GLP-1)-based drugs are approved for treatment of both obesity and type 2 diabetes (T2D), proving therapeutic importance of EECs.…”
Section: Introductionmentioning
confidence: 99%